IDENTIFIKASI JENIS TANAH DI KAWASAN GUNUNG TUJUH RESORT KERINCI UTARA, TAMAN NASIONAL KERINCI SEBLAT - Agustina, Dinda Tri; Eka Putri, Amelia Retno; Rahmatia, Citra; Kurniawan, Riko (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
Indonesia is known as the country that has the most active volcanoes, namely 30% in the world. The type of igneous rock determines the type and characteristics of the soil that will be formed. The soil in Indonesia's tropical forest volcano areas is dominated by volcanic soil or Andosol soil. The TNKS area is one of the areas that has Andosol soil. This research was conducted in March 2024 and was located in the lower mountain area of the Gunung Tujuh Region, Kerinci Seblat National Park using a field survey method. The stages of this research include taking soil samples in 6 layers with a height of each soil being 20 cm. The soil that has been taken is then analyzed using the Munsell Soil Color Chart book and the sense of touch directly. The research results show that the Hue value is the same in each layer, namely 7.5 YR and the color shows differences according to the depth of the soil, namely very dark, strong black, strong brown and dark brown. The soil structure is dominated by a crumb structure and texture of sandy loam, dusty clay loam and clay loam.